Characterising and describing postpartum haemorrhage emergency kits in context: a protocol for a mixed-methods study. Issue 4 (19th April 2021) - Woodward, Matthew; Ansari, Akbar; Draycott, Tim; Winter, Cathy; Marjanovic, Sonja; Dixon-Woods, Mary
Abstract : Introduction: Postpartum haemorrhage (PPH) is an obstetric emergency requiring prompt and accurate response. PPH emergency kits containing equipment and medications can facilitate this kind of intervention, but their design and contents vary, potentially introducing risk of confusion or delay. Designs may be suboptimal, and relying on localised kit contents may result in supply chain costs, increased waste and missed opportunities for economies of scale. This study aims to characterise contextual influences on current practice in relation to PPH kits and to describe the range of kits currently employed in UK maternity units. Methods and analysis: This mixed-methods study comprises two phases. The first will use field observations and semistructured interviews to research PPH kits in a small number (3–5) of maternity units that will be selected to represent diversity. Analysis will be conducted both using an established human factors and ergonomics framework and using the constant comparative method for qualitative data analysis. The second phase will use a research and development platform (Thiscovery) to conduct a crowdsourced photography-based audit of PPH kits currently in use in the UK. Participants will tag images to indicate which objects have been photographed. Quantitative analysis will report the frequency of inclusion of each item in kits and the content differences between kit and unit types. All maternity units in the UK will be invited to take part, with additional targeted recruitment strategies used, if necessary, to ensure that the final sample includes different maternity unit types, sizes and PPH kit types. Study results will inform future work to develop consensus on effective PPH kit designs. Ethics and dissemination: Approval has been received from the UK Health Research Authority (project ID 274147). Study results will be reported through the research institute's website, presented at conferences and published in peer-reviewed journals.